The Effectiveness of the Active Debate Method on Speaking Skills in the Social Sciences Subject of Elementary School Students : Efektivitas Metode Debat Aktif Terhadap Keterampilan Berbicara Di Mata Pelajaran Ips Siswa Sekolah Dasar - Hijayanti, Amalia Nova; Rezania, Vanda (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effectiveness of the active debate method on students' speaking skills in elementary school social studies subjects, the type of research used in this thesis is to use the type of literature study research. The research method used by researchers is to collect research data in the form of library data that has been selected, searched, presented and analyzed. The results of this study were the effectiveness of the active debate method affecting the speaking skills of elementary school students, as evidenced by the results of the study: H1 was accepted and Ho was rejected, because H1 had a p value <0.05, so it could be concluded that the experimental class using the method was better. debate because students can quickly hone their speaking skills, and can provide students to be able to think logically, rationally, and make students more active and interactive in issuing an idea or opinion, so that it becomes easier for students to accept and think critically about questions which was brought up by the interlocutor.